Do Dividend Policy and Leverage Play a Role in Firm Value Creation? - Nurfauziah Nurfauziah; Mohamad Saparudin; Maryanta Maryanta (Journal of Business, Management, & Accounting, 2022)
This study is a comprehensive synthesis of relevant prior researches. The goal of this study was to examine the role of leverage and dividend policy in increasing the firm value of insurance companies. This study's population consisted of 17 insurance companies that were listed on the Indonesia Stock Exchange between 2016 and 2020. The purposive sampling method was used to select seven companies for this study. Multiple linear regression was used in SPSS 25 to analyze the collected data. The findings revealed that leverage had a negative impact on firm value, whereas dividend policy had a positive impact on firm value. The model proposed in this study could explain 38.9 percent of the firm's value